Internalisation and toxicity of amyloid‐β 1‐42 are influenced by its conformation and assembly state rather than size. Issue 21 (11th September 2020) - Vadukul, Devkee M.; Maina, Mahmoud; Franklin, Hannah; Nardecchia, Astrid; Serpell, Louise C.; Marshall, Karen E.
Abstract : Amyloid fibrils found in plaques in Alzheimer's disease (AD) brains are composed of amyloid‐β peptides. Oligomeric amyloid‐β 1‐42 (Aβ42) is thought to play a critical role in neurodegeneration in AD. Here, we determine how size and conformation affect neurotoxicity and internalisation of Aβ42 assemblies using biophysical methods, immunoblotting, toxicity assays and live‐cell imaging. We report significant cytotoxicity of Aβ42 oligomers and their internalisation into neurons. In contrast, Aβ42 fibrils show reduced internalisation and no toxicity. Sonicating Aβ42 fibrils generates species similar in size to oligomers but remains nontoxic. The results suggest that Aβ42 oligomers have unique properties that underlie their neurotoxic potential. Furthermore, we show that incubating cells with Aβ42 oligomers for 24 h is sufficient to trigger irreversible neurotoxicity. Abstract :